The pattern of distant metastasis and clinicopathological factors associated with de-novo metastatic cervical cancer: a retrospective analysis - Kannan, J.; Saklani, Amit; Mohanty, Srigopal; Narapaneni, Kiranmayee; George, Deepak; Ingersal, N. (International Journal of Research in Medical Sciences, 2021)
Background: Metastatic cervical cancer carries poor prognosis. The factors associated with distant metastasis in newly diagnosed cervical cancer patients are not clear. Methods: A retrospective analytical study was performed to study the pattern of distant metastasis, and to evaluate the factors associated with de-novo metastatic cervical cancer. Univariate and multivariate analysis (by MANOVA) were used to evaluate the association. P≤0.05 was considered significant. Results: Out of 1321 newly diagnosed cervical cancer patients, 54 (4.1%) had de-novo metastatic disease and most of which (81%) were found at single site. Common sites of distant metastasis were non-regional nodes, followed by liver, lung, peritoneum and bone. Univariate analysis showed the factors associated with de-novo metastasis were non squamous subtype, high grade histology, bulky primary tumor (>4 cm), pelvic/para-aortic lymphadenopathy, and hydroureteronephrosis. Multivariate analysis revealed the factors associated with de-novo metastasis were bulky primary tumor (>4 cm), high grade histology, pelvic/para aortic lymphadenopathy, hydroureteronephrosis. Conclusions: Newly diagnosed cervical cancer patients with bulky primary tumor, high grade histology, pelvic or para aortic lymphadenopathy, hydroureteronephrosis are associated with higher risk of de-novo distant metastasis.